Rasa Koherensi Terkait Pekerjaan di Kalangan Dosen dan Staf Pendidikan - Wahyu Agung Budi Alamsyah; Andik Supriyatno; Muhammad Rafli Aidillah; Muhammad Henry Gunawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to measure the level of Work-SOC (Sense of Coherence at work) among lecturers and administrative staff at a private health-focused higher education institution in Samarinda, East Kalimantan, and to examine whether there were significant differences between the two groups regarding this measure. A descriptive-analytic design with a cross-sectional approach was employed. The results showed that the majority of respondents fell into the low category (56.9%), with